A Comparative‐Advantage Approach to Government Debt Maturity. (August 2015) - GREENWOOD, ROBIN; HANSON, SAMUEL G.; STEIN, JEREMY C.
ABSTRACT We study optimal government debt maturity in a model where investors derive monetary services from holding riskless short‐term securities. In a setting where the government is the only issuer of such riskless paper, it trades off the monetary premium associated with short‐term debt against the refinancing risk implied by the need to roll over its debt more often. We extend the model to allow private financial intermediaries to compete with the government in the provision of short‐term money‐like claims. We argue that, if there are negative externalities associated with private money creation, the government should tilt its issuance more toward short maturities, thereby partially crowding out the private sector's use of short‐term debt.